2018
DOI: 10.1371/journal.pbio.2006450
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous Hsp90 promotes phenotypic diversity through network evolution

Abstract: Biological processes in living cells are often carried out by gene networks in which signals and reactions are integrated through network hubs. Despite their functional importance, it remains unclear to what extent network hubs are evolvable and how alterations impact long-term evolution. We investigated these issues using heat shock protein 90 (Hsp90), a central hub of proteostasis networks. When native Hsp90 in Saccharomyces cerevisiae cells was replaced by the ortholog from hypersaline-tolerant Yarrowia lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 91 publications
2
18
0
Order By: Relevance
“…We hypothesize that, within S. chilense , each NRC coevolves as a helper NLR with a specific set of sensor NLRs. In experimental evolution in yeast, major evolutionary and functional novelty has been shown to occur by changes in the hubs of a gene network (Koubkova‐Yu et al ., ). The main genes underlying habitat adaptation are often ‘helpers’ and do not on their own provide a specific recognition of the newly encountered pathogens (new species or genera) but improve signalling processes.…”
Section: Discussionmentioning
confidence: 97%
“…We hypothesize that, within S. chilense , each NRC coevolves as a helper NLR with a specific set of sensor NLRs. In experimental evolution in yeast, major evolutionary and functional novelty has been shown to occur by changes in the hubs of a gene network (Koubkova‐Yu et al ., ). The main genes underlying habitat adaptation are often ‘helpers’ and do not on their own provide a specific recognition of the newly encountered pathogens (new species or genera) but improve signalling processes.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, although evolved differences are polygenic, with no particular gene having a major effect, the rapid evolution of phenology in R. pomonella appears to have favored changes in transcription at loci with higher network conductivity than expected by chance. Recent work indeed predicts that the evolution of hub-like genes can facilitate rapid evolution by facilitating larger “jumps” in phenotypic space ( 39 , 68 ). However, the generality of this result may depend on the strength of natural selection.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al (Chen et al, 2012) demonstrated that inhibiting HSP90 can potentiate fast adaptation to cytotoxic compounds by inducing aneuploidy. Very recently, Koubkova-Yu et al (Koubkova-Yu et al, 2018) found that by replacing the native HSP90 in Saccharomyces cerevisiae cells with the ortholog from hypersaline-tolerant Yarrowia lipolytica , the evolved clones showed a wider range of phenotypic variation than cells carrying native HSP90 and some of them exhibited beneficial mutations with a higher fitness improvement.…”
Section: Discussionmentioning
confidence: 99%
“…HSP90 reduction has also been suggested to lead to transposon activation, thereby generating new genetic variation (Specchia et al, 2010). Only very few studies have so far addressed the potential adaptive value of HSP90-regulated phenotypes (Chen et al, 2012; Koubkova-Yu et al, 2018; Queitsch et al, 2002; Rohner et al, 2013). For example, in surface populations of cavefish Astyanax mexicanus , HSP90 inhibition induced variation in eye size, suggesting that the evolution of adaptive eye loss in the dark might have been facilitated by HSP90 in nature (Rohner et al, 2013).…”
Section: Introductionmentioning
confidence: 99%